2014
DOI: 10.12980/apjtb.4.2014c636
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antibacterial activity of Khaya senegalensis [(Desr.) A. Juss)] stem bark extract on Salmonella enterica subsp. enterica serovar Typhi [(ex Kauffmann and Edwards) Le Minor and Popoff]

Abstract: The antibacterial properties of K. senegalensis stem bark extract can be harnessed for the production of new antibiotics or the enhancement of already existing antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
4
5
1
Order By: Relevance
“…There is no significant difference with the results obtained by Abdallah et al, 17 who found a MIC of 50mg/ml for the aqueous extract and 25mg/ml for the ethanolic extract of the trunk bark of Khaya Senegalensis on a strain of the genus Salmonella. These values are lower than those obtained by Ugoh et al 28 who also conducted antimicrobial tests of aqueous and ethanolic extracts of the trunk bark of Khaya senegalensis and found a MIC of 200mg/ml for both extracts on a strain of Salmonella typhi. The differences observed with the other authors could be explained by several factors, including the nature of the solvents of extractions and the antimicrobial tests used.…”
Section: Resultscontrasting
confidence: 70%
“…There is no significant difference with the results obtained by Abdallah et al, 17 who found a MIC of 50mg/ml for the aqueous extract and 25mg/ml for the ethanolic extract of the trunk bark of Khaya Senegalensis on a strain of the genus Salmonella. These values are lower than those obtained by Ugoh et al 28 who also conducted antimicrobial tests of aqueous and ethanolic extracts of the trunk bark of Khaya senegalensis and found a MIC of 200mg/ml for both extracts on a strain of Salmonella typhi. The differences observed with the other authors could be explained by several factors, including the nature of the solvents of extractions and the antimicrobial tests used.…”
Section: Resultscontrasting
confidence: 70%
“…malaria [ 87 ] Antibacterial activity against S. enterica subsp. Enterica serovar typhi (50% ethanolic leaf extract) [ 171 ], in vivo hypoglycemic activity (Ethyl acetate extract) [ 172 ], hepatoprotective effects [ 173 ], antioxidant activity (Ethanolic extract) [ 174 ] in vitro (Agar well diffusion method) [ 171 ], in vivo (rats) [ 172 ], in vivo (rats) [ 173 ], in vitro (DPPH radical scavenging assay, deoxyribose assay, Nitric oxide radical scavenging assay) [ 174 ] Orally administered ethanol stem bark extract in rats at a dose of 2 mg/kg for 18 days was reported to induce the synthesis of liver enzymes [ 175 ]. The subchronic administration of the aqueous stem bark extract to rats was reported to affect the cellular integrity of vital organs of the body [ 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…Malaria [99,109], constipation, jaundice [65], aphrodisiac, general wellbeing [14], sexually transmitted Infections [67] The acetone stem bark extract showed antibacterial activity against Proteus mirabilis [64], the aqueous pulp extract showed antibacterial activity against S. aureus, E. coli and P. aureginosa [110], tannins, phlobatamins, alkaloids, saponins, and sesquiterpenes were found present [64] Tylosema fassoglense (Kotschy ex Schweinf.) Torre & Hillc.…”
Section: Graymentioning
confidence: 99%